Doing the Right Thing or Doing the Thing Right: Implications of Participant Withdrawal. (July 2014) - Thorpe, Andrea Stevenson
This article discusses implications of participant withdrawal for inductive research. I describe and analyze how a third of my participants withdrew from a grounded theory study. I position my example, ensuing issues, and potential solutions as reflective of inductive methodologies as a whole. The crux of the problem is the disruption inflicted by withdrawal on inductive processes of generating knowledge. I examine the subsequent methodological and ethical issues in trying to determine the best course of action following withdrawal. I suggest three potential options for researchers: Continuing the study with partial data, continuing the study with all data, and discontinuing the study. Motivated by my experience, and wider theoretical considerations, I present several suggestions and questions, with the aim of supporting researchers in determining the best course of action for their individual field circumstances.